Pakistan - Strategic Environmental, Poverty and Social Assessment of Trade and Transport Sector Reforms - World Bank (Washington, DC, 2013)
The Government of Pakistan's (GoP's) 2011 framework for economic growth seeks to place Pakistan on a sustained high economic growth path of 7 percent per year through measures to reduce the cost of doing business, improve the investment climate, and strengthen institutions. Trade and transport reforms are central to achieve the Framework's goal. The transport sector constitutes 10 percent of Pakistan's Gross Domestic Product (GDP) and provides 6 percent of the employment in the country. The sector plays an important role in linking other sectors in the economy, contributes to both domestic and international trade, and helps facilitate the spatial transformation occurring in Pakistan. However, present patterns in transport and trade logistics generate inefficiencies that are costing Pakistan's economy roughly 4-6 percent of GDP per year, which is a major constraint to the aspirations set out in the Framework. This analytical work on Strategic Environmental, Poverty, and Social Assessment (SEPSA) of trade and transport sector reforms examines poverty, social and environmental aspects associated with reforms that would increase the freight transport sector's productivity to meet the framework goals. it focused on the following areas: (i) SEPSA's methodology and aims; (ii) description of key challenges in Pakistan's freight transport sectors, including the road, trucking, railway, port, and aviation sectors, as well as trade and transport interventions and reforms proposed by the GoP and other stakeholders; (iii) identification of stakeholders, particularly the most vulnerable groups that could be affected by reforms aimed at increasing freight transport productivity, and analyzing the priority poverty issues associated with freight transport in Pakistan; (iv) identification jointly with stakeholders of priority social and environmental issues associated with freight transport, and analyzing such issues; (iv) examination of potential freight transportation social and environmental policy options for enhancing positive effects or reducing adverse effects associated with increases in freight transport productivity; and (v) identification of options to strengthen governance and the institutional capacity of agencies to manage the environmental, social and poverty priorities associated with Pakistan's freight transportation.